2011
DOI: 10.1111/j.1365-2893.2011.01541.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphotropic hepatitis C virus has an interferon‐resistant phenotype

Abstract: Hepatitis C virus (HCV) infects and associates with B cells, leading to abnormal B-cell activation and development of lymphoproliferative and autoimmune disorders. This immune perturbation may in turn be associated with the resistance of HCV against the host immune system. The objective of this study was to analyse the effects of HCV infection of B cells on the efficacy of interferon (IFN)-based therapy. The study enrolled 102 patients with chronic hepatitis C who were treated with pegylated IFN plus ribavirin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
(52 reference statements)
2
9
1
Order By: Relevance
“…Table 2 shows the clinical characteristics of HCV-infected patients. Cryoglobulinemia was identified in 13.7 of CH-C patients who enrolled in this study, and this prevalence was lower than that previously reported 24 22 . A high prevalence of hypocomplementemia low C3 33.6 , low C4 10.6 , low CH50 59.3 , and high levels of RF 37.6 were detected in the patients before DAAs administration, and interestingly, these findings were identical to the previous report.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Table 2 shows the clinical characteristics of HCV-infected patients. Cryoglobulinemia was identified in 13.7 of CH-C patients who enrolled in this study, and this prevalence was lower than that previously reported 24 22 . A high prevalence of hypocomplementemia low C3 33.6 , low C4 10.6 , low CH50 59.3 , and high levels of RF 37.6 were detected in the patients before DAAs administration, and interestingly, these findings were identical to the previous report.…”
Section: Discussioncontrasting
confidence: 80%
“…It has been proven epidemiologically that HCV causes a variety of extrahepatic manifestations, including cardiovascular diseases and dysfunction of the central nervous system 15 . In these manifestations, LPDs are most closely associated with HCV infection [22][23][24] . Zignego et al 25 reported the t 14 ; 18 translocation and overexpression of bcl-2 in lymphoid cells of patients with a lymphoproliferative disorder associated with HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports indicate that HCV can efficiently infect extra‐hepatic tissue, including PBMCs . This and other observations collectively suggest that PBMCs may represent a privileged reservoir for HCV. Notably, a recent study demonstrated that host‐based resistance to RBV may occur in HCV patients undergoing combination PegIFN/RBV therapy .…”
Section: Discussionmentioning
confidence: 87%
“…Some reports, however, do suggest that HCV persists, albeit at very low levels, in circulating lymphoid cells for several years after apparently complete clinical and virological resolution of chronic hepatitis C, suggesting that PBMCs represent a natural reservoir for HCV . Recent reports suggest that HCV‐infected lymphoid cells are resistant to IFN and RBV , suggesting a link between the presence of HCV RNA in PBMCs with a poor response to IFN therapy . Yet, again these observations remain highly controversial .…”
Section: Introductionmentioning
confidence: 99%
“…1A 5 . RNA 1 µl from peripheral blood mononuclear cells derived from the patients with CH-B was reverse transcribed into cDNA and amplified using the GeneAmp EZ rTth RNA polymerase chain reaction kit Applied Biosystems, Inc., Foster City, CA , according to the manufacturer s instructions.…”
Section: Amplification Of Ig-vh Region By Polymerase Chain Reaction Amentioning
confidence: 99%